A coleta seletiva domiciliar do município de Soure-PA como elemento de proteção e sustentabilidade ambiental - SILVA, Walcilene Santos (2019)
This work is related to researches concerning environmental management, aiming to approach the process of recyclable waste collection at the city of Soure in the state of Pará, emphasizing its importance to the environmental preservation and sustainability. During this research it has been noticed that even if the city of Soure has an integrated project of solid waste (PGIRS) which aims to encourage the recyclable waste collection and to improve the structure of the regular garbage collection, the recyclable waste collection has not been developing in a systematic and appropriated way, this way, it can be said that it is rudimentary once most of the recyclable waste collectors, remain working in unhealthy conditions, collecting the recyclables in the sanitary land without significant improvements in their quality of life. So, when it is approached the issue regarding the landfill, it is important to say that it is inconsistent with health and environmental standards, since PGIRS points for the need to build a healthier sanitary land. One factor that has not allowed the success of recyclable waste collection in Soure is the absence of an environmental educational program, as PGIRS has proposed. From this perspective, it is noticed that the city of Soure has a long path regarding the issue of recyclable waste collection. Therefore, it would be necessary a monitoring by all the involved in this process (city council, cooperatives of recyclable waste collectors, cart-drivers, companies, schools, people) in order to do an overview about the result of such program. It is also necessary to have a qualified team, responsible for the management, storage and a survey concerning the amount of collected garbage as well as the proceeds. It is added to these and other proposals outlined at this work, it is also important to point out the proposal of realization of continuous activities of information and encouragement which will be possible to consolidate from the implementation and developing of an environmental educational program.